Multimodality Imaging to Characterize a Metastatic Cardiac Mass. Issue 5 (11th January 2016) - Yarlagadda, Bharath; Paleti, Swathi; Annamalai, Senthil Kumar
Mini‐Abstract: A 66‐year‐old male with a medical history of squamous cell carcinoma of the head and neck with recurrent metastasis and multiple interventions was found to have a lesion in the heart on positron emission tomography scan. Echocardiography showed a thrombuslike 2 × 2 cm mass attached to the right ventricle side of the septum. Contrast‐enhanced cardiac magnetic resonance imaging was obtained to better characterize the mass. It showed a metastatic infiltrative tumor in the septum with a large overlying thrombus protruding into right ventricle. Our case demonstrates the utility of multimodality imaging to characterize an unusual cardiac tumor helping guide management.